Droughts and deluges: changes in river discharge and the carbonate chemistry of an urbanized temperate estuary - Barrett, Lauren J.; Vlahos, Penny; McGuinness, Mary A.; Whitney, Michael M.; Vaudrey, Jamie M.P. (Frontiers in Marine Science, 2024)
Long Island Sound (LIS) is a highly urbanized estuary that receives high inputs of nitrogen pollution leading to summertime hypoxia in the bottom waters of its western region. Though LIS hypoxia has been well-studied for decades, there is a paucity of information regarding eutrophication-induced acidification due to the challenges of obtaining high-precision observations of the marine carbonate system. In this work, we established a time-series of carbon dioxide (CO2) system observations in LIS through measurements of dissolved inorganic carbon (DIC) and total alkalinity (TA) during thirteen sampling events between March 2020 and August 2022. This time span captured both seasonal and interannual variation, including the contrast between two historic drought years (2020 and 2022) and one high-freshwater flow year with significant tropical storm activity (2021). Observations revealed reduced acidification in western LIS (WLIS) (minimum aragonite saturation state, Ωar > 1.5) during the high-river discharge summer of 2021, corresponding to a decrease in the DIC/TA ratio of the Housatonic River. By contrast, LIS bottom water DIC and DIC/TA were higher during the drought summers of 2020 and 2022 (bottom DIC/TA = 0.9-1.0 and 0.85-0.9 in 2020 and 2021, respectively), leading to more acidified conditions and persistent aragonite undersaturation (minimum Ωar <1.0 and 1.1 in 2020 and 2022, respectively). Increased river discharge mitigated respiration-induced acidification in WLIS, likely due to a combination of decreased estuarine residence time and reduced riverine DIC/TA. These results motivate future studies of the carbonate chemistry of LIS and its freshwater endmembers in relation to hypoxia dynamics, with consideration of climate related shifts in physical and biological dynamics of the estuary with time.